Environmental assessment of the poultry sector of BRAC's ultra poor programme - Akter, Nasima; Sharmin, Lammia; Lapenna, Lily (BRAC Research and Evaluation Division (RED), 2019)
This study aimed to conduct an environmental assessment of the poultry sector of 'Challenging the Frontiers of Poverty Reduction/ Targeting the Ultra Poor Program (CFPR!fUP)' program of BRAC. Special focus was given to health and environmental aspects of poultry rearing including the housing and diseases of both human and poultry, surrounding environment, access to and sources of water, waste management, common property resources, and social conflicts related to the poultry programme. Data were collected through field observation, in-depth interview, and case studies during August 2003. Poultry rearing was found to be a promising income generating activity for the ultra poor. A few obstacles related to health, resource use, resource management, and social conflicts were identified. There were some innovative initiatives taken by the TUP poultry members related to waste management, alternate source of income and water access. Some steps were suggested to resolve social conflicts, health problems, poultry housing, waste marketing, increase nutritional intake, initiate intermediate mcome generating projects, and management issues of common property resource.